A catalog of architectural tactics for cyber-foraging - Lewis, Grace; Lago, Patricia (2015 11th International ACM SIGSOFT Conference on Quality of Software Architectures (QoSA), 2015)
Mobile devices have become for many the preferred way of interacting with the Internet, social media and the enterprise. However, mobile devices still do not have the computing power or battery life that will allow them to perform effectively over long periods of time or for executing applications that require extensive communication or computation, or low latency. Cyber-foraging is a technique enabling mobile devices to extend their computing power and storage by offloading computation or data to more powerful servers located in the cloud or in single-hop proximity. This paper presents a catalog of architectural tactics for cyber-foraging that was derived from the results of a systematic literature review on architectures for cyber-foraging systems. Elements of the architectures identified in the primary studies were codified in the form of Architectural Tactics for Cyber-Foraging. These tactics will help architects extend their design reasoning towards cyber-foraging as a way to support the mobile applications of the present and the future.